Experimental and Quantum Mechanical Characterization of an Oxygen‐Bridged Plutonium(IV) Dimer. Issue 36 (5th June 2020) - Ray, Debmalya; Xie, Jing; White, Jacob; Sigmon, Ginger E.; Gagliardi, Laura; Hixon, Amy E.
Abstract: We report the synthesis and characterization of K4 {[PuCl2 (NO3 )3 ]2 (μ2 ‐O)}⋅H2 O, which contains the first known μ2 ‐oxo bridge between two Pu IV metal centers. Adding to its uniqueness is the Pu−(μ2 ‐O) bond length of 2.04 Å, which is the shortest of other analogous compounds. The Pu−(μ2 ‐O)−Pu bridge is characterized by the mixing of s ‐, d ‐, and p ‐orbitals from Pu with the p ‐orbitals of O; the 5 f ‐orbitals do not participate in bonding. Natural bond orbital analysis indicates that Pu and O interact through one 3c‐2e σPu‐O‐Pu and two 3c‐2e πPu‐O‐Pu bonding orbitals and that the electron density is highly polarized on the μ2 ‐O. Bond topology properties analysis indicates that the Pu−(μ2 ‐O) bond shares both ionic and covalent character. Quantum mechanical calculations also show that the dimer has multiconfigurational ground states, where the nonet, septet, quintet, triplet, and singlet are close in energy. This work demonstrates the interplay between experimental and computational efforts that is required to understand the chemical bonding of Pu compounds. Abstract : A μ2 ‐oxo‐bridged Pu IV dimer species was isolated and characterized for the first time. The Pu‐(μ2 ‐O)‐Pu bridge is nearly linear and the Pu−(μ2 ‐O) bond length is shorter than other similar f ‐element compounds. An analysis of the dimer's electronic structure shows that the electron density is highly polarized on the bridging oxygen, the Pu−(μ2 ‐O) bond is both ionic and covalent in nature, and the f ‐orbitals do not participate in bonding.